Circadian Rhythm Disruption Increases Tumor Growth Rate and Accumulation of Myeloid‐Derived Suppressor Cells. Issue 9 (2nd June 2022) - Roberts, Nathan T.; MacDonald, Cameron R.; Mohammadpour, Hemn; Antoch, Marina P.; Repasky, Elizabeth A.
Abstract: Circadian rhythm disruption is implicated in the initiation and progression of many diseases, including cancer. External stimuli, such as sunlight, serve to synchronize physiological processes and cellular functions to a 24‐h cycle. The immune system is controlled by circadian rhythms, and perturbation of these rhythms can potentially alter the immune response to infections and tumors. The effect of circadian rhythm disruption on the immune response to tumors remains unclear. Specifically, the effects of circadian disruption (CD) on immunosuppressive cell types within the tumor, such as myeloid‐derived suppressor cells (MDSCs), are unknown. In this study, a shifting lighting schedule is used to disrupt the circadian rhythm of mice. After acclimation to lighting schedules, mice are inoculated with 4T1 or B16‐F10 tumors. Tumor growth is increased in mice housed under circadian disrupting lighting conditions compared to standard lighting conditions. Analysis of immune populations within the spleen and tumor shows an increased accumulation of MDSCs within these tissues, suggesting that MDSC mediated immunosuppression plays a role in the enhanced tumor growth caused by circadian disruption. This paves the way for future studies of the effects of CD on immunosuppression in cancer. Abstract : Disruption of mouse circadian rhythm increases tumor growth. Circadian disruption also increases the accumulation of myeloid‐derived suppressor cells (MDSCs) in the tumors. The increased accumulation of MDSCs likely results in greater suppression of anti‐tumor immune cells within the tumor and contributes to the enhanced growth seen in circadian disrupted mice.